Multi-System Adaptation to Confinement During the 180-Day Controlled Ecological Life Support System (CELSS) Experiment - Yuan, Ming; Custaud, Marc-Antoine; Xu, Zi; Wang, Jingyu; Yuan, Min; Tafforin, Carole; Treffel, Loïc; Arbeille, Philippe; Nicolas, Michel; Gharib, Claude; Gauquelin-Koch, Guillemette; Arnaud, Laurent; et al. (Frontiers in Physiology, 2019)
Confinement experiments are essential to prepare long-term space exploration. The 180-day Chinese CELSS (Controlled Ecological Life Support System) study is unique in its design, including a closed-loop system and mid-mission simulation of Mars-like day–night cycle of 24 h 40 min for 36 days (days 72–108). Our aim was to study physiological and psychological consequences of this confinement in four healthy volunteers (one female). CELSS platform consisted of six interconnected modules including four greenhouses. Life support systems were controlled automatically. Body composition, fluid compartments, metabolic state, heart, large vessels, endothelial function, and muscle tone were studied using biological, functional, and/or morphological measurements. Behavioral activities were studied by ethological monitoring; psychological state was assessed by questionnaires. Body weight decreased by ∼2 kg mostly due to lean mass loss. Plasma volume and volume-regulating hormones were mostly stable. Carotid intima-media thickness (IMT) increased by 10–15%. Endothelium-dependent vasodilation decreased. Masseter tone increased by 6–14% suggesting stress, whereas paravertebral muscle tone diminished by 10 ± 6%. Behavioral flow reflecting global activity decreased 1.5- to 2-fold after the first month. Psychological questionnaires revealed decrease in hostility and negative emotions but increase in emotional adaptation suggesting boredom and monotony. One subject was clearly different with lower fitness, higher levels of stress and anxiety, and somatic signs as back pain, peak in masseter tone, increased blood cortisol and C-reactive protein. Comparison of CELSS experiment with Mars500 confinement program suggests the need for countermeasures to prevent increased IMT and endothelial deconditioning. Daily activity in greenhouse could act as countermeasure against psycho-physiological deconditioning.